Glucose Levels in At-risk Newborns (GLEAN): a prospective cohort study on glucose profiles in infants at risk of hypoglycemia - Fabian Yap; Fabian Yap; Fabian Yap; Daniel Chan; Daniel Chan; Daniel Chan; Ruther Teo Zheng; Lakshmi Shandra Bos; Victor Samuel Rajadurai; Victor Samuel Rajadurai; Victor Samuel Rajadurai; Suresh Chandran; et al. (Frontiers in Endocrinology)
ObjectiveTo describe glucose patterns in at-risk infants, determine the incidence of hypoglycemia across different risk groups, and evaluate the impact of combined risk factors on odds of developing hypoglycemia.Study designThis prospective cohort study was conducted at KK Women’s and Children’s Hospital from 16 December 2019 to 16 March 2020, during which 2,564 babies were born. Of these, 701 were identified as at-risk of hypoglycemia based on predefined clinical criteria: infants of diabetic mothers (IDM), term infants with birth weight >4000 g or <2600 g, preterm infants, and infants of obese mothers (IOM). Risk group classification was refined using INTERGROWTH-21st standards, and infants were further stratified by the presence of single or combined risk factors. Complete glucose measurements at 2, 6, 12, 18, and 24 hours were available for 670 infants (95.6%). The primary outcomes were glucose trends and the incidence of hypoglycemia, defined as blood glucose < 3.0 mmol/L.ResultsMean glucose levels stabilized between 3.8 and 4.0 mmol/L by 24 hours. The highest incidence of hypoglycemia was observed in single risk factor SGA infants (22.6%), followed by IOM (16%), a group less studied in hypoglycemia risk assessments. This was comparable to the incidence seen in IDM (13.0%). In contrast, single risk factor LGA infants exhibited the lowest incidence of hypoglycemia (6.2%). Infants with combined risk factors had a higher incidence of hypoglycemia compared to those with a single risk factor (18.5% vs 15.9%) and showed higher odds of hypoglycemia compared to those with a single risk factor (OR 2.47; 95% CI: 0.98–6.08, p = 0.049).ConclusionsGlucose trajectories and hypoglycemia risks differ across clinically defined at-risk groups, underscoring the importance of targeted screening and management protocols. Stratifying infants by single and combined risk factors provided additional insight that may support future refinements to neonatal hypoglycemia clinical guidelines.